บ้านใต้ถุนสูงรับมือน้ำท่วมซ้ำซากตามหลักเศรษฐกิจพอเพียง: กรณีศึกษาบางระกำโมเดล: Elevated Detached House for Handling Repeated Floods Based on Sufficiency Economy: A Case Study of Bang-Rakam Model - Promma, Kitchakarn (Asian Health, Science and Technology Reports, 2014)
บางระกำโมเดลเกิดจากน้ำท่วมใหญ่ พ.ศ. 2554 ที่อำเภอบางระกำ จังหวัดพิษณุโลก ก่อนที่น้ำจะไหลเข้าท่วมที่ราบภาคกลางและกรุงเทพฯ รัฐบาลยกให้บางระกำโมเดลเป็นต้นแบบของการแก้ไขปัญหาน้ำท่วม ที่ผ่านมารัฐบาลมุ่งจะก่อสร้างโครงการทางวิศวกรรมขนาดใหญ่ การกระตุ้นให้ประชาชนปลูกสร้างหรือดัดแปลงบ้านเดิมให้เป็นบ้านชั้นเดียวใต้ถุนสูงเหมือนในอดีตและสนับสนุนการปรับเปลี่ยนวิถีชีวิตให้เข้ากับสภาวะน้ำท่วมซ้ำซากได้ดียิ่งขึ้นแทนโครงการก่อสร้างขนาดใหญ่นั้นน่าจะเป็นแนวทางการแก้ไขปัญหาน้ำท่วมซ้ำซากได้หรือไม่ วัตถุประสงค์ของการวิจัยนี้คือเพื่อสำรวจความเป็นไปได้เรื่องการดัดแปลงบ้านเดิมให้เป็นบ้านใต้ถุนสูงรวมทั้งการปรับตัวเข้ากับน้ำท่วมซ้ำซากในบางระกำโมเดล จากการออกแบบสอบถามกับกลุ่มตัวอย่างของผู้ประสบภัยจำนวน 158 ครัวเรือนในตำบลชุมแสงสงคราม คุยม่วง บางระกำ ท่านางงาม และวังอิทก พบว่า ผู้ประสบภัยมีเหตุผลดี มีความพอประมาณ แต่มีภูมิคุ้มกันต่ำ บ้านเรือน 41% เป็นบ้านไม้ชั้นเดียวมีใต้ถุนสูงอยู่ก่อนน้ำท่วม และใช้เรือเป็นพาหนะในการเดินทางในช่วงที่มีน้ำท่วมขัง ระดับพื้นเรือนสูงกว่าพื้นดินเฉลี่ย 2.7 เมตร ในบรรดาบ้านใต้ถุนสูง 74 หลัง มีรอดพ้นน้ำท่วม 78% ซึ่งพื้นเรือนสูงกว่าคราบน้ำท่วมเฉลี่ย 1.1 เมตร แต่มีบ้านที่ถูกน้ำท่วม 22% ซึ่งพื้นเรือนต่ำกว่าคราบน้ำท่วมเฉลี่ย 0.4 เมตร ผู้ประสบภัยกลุ่มนี้จึงต้องการให้รัฐบาลช่วยดีดบ้านเรือนให้สูงพ้นน้ำท่วมอย่างน้อยอีก 1.5 เมตร Bang-Ragam Model was formed after the megaflood of 2011 at Bang-Rakam, Phitsanulok before the flood flewed downstream to the central plain and Bangkok. The government uses the Bang-Ragam Model as a role model to solve flood problems. In the past, the government aims at building mega-engineering projects. Is it possible to stimulate people to build or modify their houses to be elevated detached houses like those in the past and promote human adjustment to repeated flood rather than building the maga-projects. The objectives of this study were to explore feasibility to build or modify houses to be elevated detached houses and to urge human adjustment to repeated flood in the Bang-Rakam Model. Based on questionnaires of 158 samples in Chumsaengsongkam, Kuimuang, Bang-Rakam, Thanang-Ngarm, and Wang-Itok Districts, results show that they were reasonable and self-sufficient but lack of immunity. Forty-one percent of the sampled houses are of elevated detached house type while using a boat for transportation. The average of house floor is 2.7 m above the ground. Among 74 elevated detached houses, 78% was safe from the flood with the floor 1.1 m higher than the flood level but 22% submersed with an average of 0.4 m under water. These people ask the government to raise their houses over water at least 1.5 m.